PENGARUH PROFITABILITAS DAN LEVERAGE KEUANGAN TERHADAP RETURN SAHAM PADA PERUSAHAAN INDUSTRI KONSUMSI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Roy Budiharjo (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2018)
The purpose of this study is to determine the effect of return on assets (ROA), return on equity (ROE) and debt to equity ratio (DER) to stock prices. Secondary data were collected by sample from a group of consumer goods manufacturing industries listed on the Indonesian stock exchanges for the period 2014 - 2016. Sampling in this research use purposive sampling method with criterion as (1) listed in Indonesia Stock Exchange year 2014 - 2016. (2) always looks annual financial report during period 2014 - 2016. (3) always have advantage. Data required in this study were taken from Indonesian Capital Market Directory (ICMD) 2014-2016. This study uses multiple linear regression analysis where for partial test using t test and simultaneous test using anova statistic test. The statistical test is done by t test and multiple linear regression analysis, before this test is done first classical assumption test. The result of the research shows that: 1) Based on partial research result, it can be seen that the amount of return on assets (ROA) produced by the company has no significant effect on stock return; 2) Based on the results of partial research, it can be seen that the return on equity (ROE) of the company has no significant effect on stock returns; 3) Based on the results of partial research, it can be seen that the debt to equity ratio (DER) has a positive and insignificant effect on stock returns.